Filtration assisted pretreatment for rapid enrichment and accurate detection of Salmonella in vegetables - Bin Li; Hanling Wang; Jianguo Xu; Wei Qu; Li Yao; Bangben Yao; Chao Yan; Wei Chen (Food Science and Human Wellness)
Rapid detection of target foodborne pathogens plays more and more significant roles in food safety, which requires the efficiency, sensitivity, and accuracy. In this research, we proposed a new strategy of isothermal-molecular-amplification integrated with lateral-flow-strip for rapid detection of Salmonella without traditional enrichment-culture. The designed syringe-assisted-filtration can contribute to simultaneous collection and concentration of target bacterium from vegetable samples in just 3 min, resolving the drawbacks of traditional random sampling protocols. After simple and convenient ultrasonication, samples can be directly amplified at 39 °C in 25 min and the amplicons are qualitatively and quantitatively analyzed with the designed lateral-flow-strip in 5 min. Finally, satisfied results have been achieved within 40 min, which greatly improve the efficiency while the accuracy is also guaranteed. Furthermore, all detection steps can be completed under instrument-free conditions. This method will hold great promise for target pathogen detection in the resource-limited district, or for emergency on-site identification.